Preoperative Planning of Craniectomy and Reconstruction using 3D Printed Cranioplasty for Treatment of Calvarial Lesion - Hossain, S M Monir; Khalil, Md Ibrahim; Subhan, Kazi Irfan; Hasanuzzaman, Md; Hasan, Md Mahmudul; Hasan, Md Motasimul (Bangladesh Journal of Neurosurgery, 2024)
There is a number of diseases which causes calvarial lesion. Fibrous dysplasia, intraosseous meningioma, osteoma is to name a few. Treatment of these lesions necessitates removal of part of the skull or craniectomy to decompress the brain and neural elements. The ensuing skull defect needs to be repaired to protect the brain. Previously used allograft and alloplastic materials have been replaced with newer PEEK material, which is more resistant, biocompatible and can be 3D printed. In this series we describe 4 cases in which skull lesions are removed and reconstructed in the same sitting using 3D printed PEEK implant designed preoperatively using high resolution CT data. The results are superior and complication rates are low. All the cases were done in different government hospitals. The technical process was developed indigenously, and the methods are the first in our country. Bang. J Neurosurgery 2024; 13(2): 64-69